Sea-urchin-like iron-cobalt phosphide as an advanced anode material for lithium ion batteries. Issue 19 (8th August 2022) - Pathak, Prakash Kumar; Joshi, Ved Prakash; Kumar, Nitish; Salunkhe, Rahul R.
Abstract : Highly stable iron-cobalt phosphide sea-urchins for high performance lithium ion batteries. Abstract : Lithium-ion batteries (LIBs) are the most advanced and well-developed renewable energy storage solutions over the last three decades. Resourceful and cost-effective transition metal phosphides (TMPs) have gained immense attention for various energy storage devices due to their excellent electrochemical properties. Here, we report a bimetallic phosphide (iron-cobalt phosphide, FeCoP) synthesized by a simple hydrothermal method followed by a low-temperature phosphorization. We have used this material as the anode for LIBs with lithium foil as the counter and reference and 1 M lithium hexafluorophosphate (LiPF6 ) in a mixture of EC : DMC (1 : 1) as the electrolyte. The electrochemical tests reveal that the device exhibited an excellent discharge capacity of 1653.4 mA h g −1 at a current density of 100 mA g −1 . The device retained about 80% of its performance even after 1000 cycles at a current density of 5 A g −1 . The performance of the synthesized material shows that TMPs are of great use for the application of LIBs.